Symbols of Slavery in the Qur'an and Its Relation to the Declaration of Human Rights - Najib, Muhamad; Taufiq, Wildan; Rusmana, Dadan (Jurnal Iman dan Spiritualitas, 2024)
This research aims to find out the symbols of slavery in the Qur'an, the semiotic perspective of Roland Barthes and its relation to the Universal Declaration of Human Rights. This study uses qualitative descriptive methods and approaches with the analysis of Roland Barthes' semiotic theory that a symbol is a sign that is surrounded by other signs so that it becomes clearer. There are two stages: the first stage is called the linguistic system, and the second stage is called the mythical system. Myth, in Barthes' view, is assumed to be a system of markers built on three things signifier, signified and sign. The results of the study show that the symbol of Abdun and Amah as human beings who have rights and obligations, the symbol of Raqabah is a valuable item that must be paid, in the sense that it must be liberated or liberated and the symbol of Ma Malakat Ayman as a halal biological channel, a companion who is allowed to marry, and a human being who has rights. As for the relationship with the Universal Declaration of Human Rights, the two have the same spirit to abolish and eliminate slavery on the face of the earth.